2008
DOI: 10.1371/journal.ppat.1000117
|View full text |Cite|
|
Sign up to set email alerts
|

Legionella Eukaryotic-Like Type IV Substrates Interfere with Organelle Trafficking

Abstract: Legionella pneumophila, the causative agent of Legionnaires' disease, evades phago-lysosome fusion in mammalian and protozoan hosts to create a suitable niche for intracellular replication. To modulate vesicle trafficking pathways, L. pneumophila translocates effector proteins into eukaryotic cells through a Type IVB macro-molecular transport system called the Icm-Dot system. In this study, we employed a fluorescence-based translocation assay to show that 33 previously identified Legionella eukaryotic-like gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
321
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(339 citation statements)
references
References 74 publications
15
321
1
2
Order By: Relevance
“…Therefore, many groups started functional studies focusing on these proteins and within a short period of time the importance of the eukaryotic-like proteins for the virulence of Legionella was shown (de Felipe et al 2008;Nora et al 2009;Hubber and Roy 2010). The main secretion system of Legionella, essential for intracellular growth, is the type IVB Dot/Icm secretion system (Marra and Shuman 1992;Berger and Isberg 1993).…”
Section: Eukaryotic-like Proteins Of Legionella Are Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many groups started functional studies focusing on these proteins and within a short period of time the importance of the eukaryotic-like proteins for the virulence of Legionella was shown (de Felipe et al 2008;Nora et al 2009;Hubber and Roy 2010). The main secretion system of Legionella, essential for intracellular growth, is the type IVB Dot/Icm secretion system (Marra and Shuman 1992;Berger and Isberg 1993).…”
Section: Eukaryotic-like Proteins Of Legionella Are Virulence Factorsmentioning
confidence: 99%
“…The main secretion system of Legionella, essential for intracellular growth, is the type IVB Dot/Icm secretion system (Marra and Shuman 1992;Berger and Isberg 1993). Using many dif-ferent methods it has been shown that at least 275 L. pneumophila proteins are secreted by this system (Campodonico et al 2005;de Felipe et al 2005;Shohdy et al 2005;de Felipe et al 2008;Burstein et al 2009;Heidtman et al 2009;Zhu et al 2011), which represents nearly 10% of the protein-coding genes predicted in the L. pneumophila genomes. At least 75 of these are eukaryotic-like proteins or carry eukaryotic domains and, for certain of these, it has also been shown experimentally that they interfere with host-cell signaling pathways ( Table 2).…”
Section: Eukaryotic-like Proteins Of Legionella Are Virulence Factorsmentioning
confidence: 99%
“…Our efforts with these strategies have led to the retrieval of 57 C. burnetii T4SS substrate candidates. Using independent translocation assays based on the Cya (18) or the β-lactamase (TEM1)-mediated FRET on CCF4-AM (6,19), we demonstrated that 32 of these proteins are translocated into host cells by the L. pneumophila Dot/Icm system.…”
mentioning
confidence: 99%
“…Various strategies have led to the identification of more than 150 protein substrates for the L. pneumophila T4SS (5-7). These proteins are predicted to modulate various host processes, including apoptosis, ubiquitination (8)(9)(10), lipid metabolism, and membrane trafficking (6,(11)(12)(13). By combining bioinformatics tools with the use of Legionella as a surrogate host to measure protein translocation, 11 Coxiella proteins containing the ankyrin repeat motif have been identified as substrates of its Dot/ Icm transporter (11,14).…”
mentioning
confidence: 99%
“…Within both evolutionarily distant host cells, L. pneumophila evades endocytic fusion and intercepts ER to Golgi vesicle traffic to remodel its phagosome into an ER-derived vacuole (Kagan and Roy, 2002;Molmeret et al, 2005;Shin and Roy, 2008;Isberg et al, 2009). The Dot/Icm type IV secretion system (Segal et al, 1998;Vogel et al, 1998) injects into the host cell a cadre of 200 effectors to modulate a myriad of cellular processes to reprogram the host cell into a proliferation niche (de Felipe et al, 2008;Shin and Roy, 2008;Isberg et al, 2009). The Ankyrin B (AnkB) effector is injected into the host cell by the Dot/Icm system upon bacterial attachment to the plasma membrane and exploits an evolutionarily conserved eukaryotic machinery within mammalian and protozoan cells (Price et al, 2009).…”
mentioning
confidence: 99%